Criminal liability in the 19th century, an issue in dispute (Ágora Journal, 2025)
This text analyzes the epistemological, professional and political disputes between Law and Medicine around the issue of criminal liability in Brazil, between the end of the 19th century and the beginning of the 20th century. It focuses on articles and books by the main jurists of the period, analyzing them critically, from the context of the advancement of hygienist and positivist ideology.
Keywords: Law; Medicine; Criminal Liability; 19th century.